Combined Magnetic Resonance Imaging and Photodynamic Therapy Using Polyfunctionalised Nanoparticles Bearing Robust Gadolinium Surface Units. Issue 20 (18th March 2020) - Chabloz, Nicolas G.; Perry, Hannah L.; Yoon, Il‐Chul; Coulson, Andrew J.; White, Andrew J. P.; Stasiuk, Graeme J.; Botnar, René M.; Wilton‐Ely, James D. E. T.
Abstract: A robust dithiocarbamate tether allows novel gadolinium units based on DOTAGA ( q =1) to be attached to the surface of gold nanoparticles (2.6–4.1 nm diameter) along with functional units offering biocompatibility, targeting and photodynamic therapy. A dramatic increase in relaxivity ( r 1 ) per Gd unit from 5.01 mm −1  s −1 in unbound form to 31.68 mm −1  s −1 (10 MHz, 37 °C) is observed when immobilised on the surface due to restricted rotation and enhanced rigidity of the Gd complex on the nanoparticle surface. The single‐step synthetic route provides a straightforward and versatile way of preparing multifunctional gold nanoparticles, including examples with conjugated zinc–tetraphenylporphyrin photosensitizers. The lack of toxicity of these materials (MTT assays) is transformed on irradiation of HeLa cells for 30 minutes (PDT), leading to 75 % cell death. In addition to passive targeting, the inclusion of units capable of actively targeting overexpressed folate receptors illustrates the potential of these assemblies as targeted theranostic agents. Abstract : Enhancing contrast : The straightforward synthesis of multifunctional nanoparticles combines the robust attachment of gadolinium units for enhanced MRI contrast with photodynamic therapy.